2009
DOI: 10.3354/meps07933
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus insecticides are not acutely harmful to corals and sponges

Abstract: Bacillus thuringiensis is a Gram-positive bacterium that produces crystalline endotoxins and is widely considered an environmentally safe insecticide to control mosquitoes and a number of agriculture pests. Bacteria closely related to B. thuringiensis have recently been discovered in association with diseased sponges, which has raised concerns that Bacillus insecticides may be harmful to tropical marine invertebrates. We exposed coral larvae and juvenile corals to the insecticides VectoBac ® G (containing B. t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The authors of that study speculate that bacterial pesticide pollution from agriculture may have introduced new bacteria that were pathogenic to sponges. Subsequent research with sponges and corals showed that addition of up to 5,000 g of the pesticides VectoBac G (containing B. thuringiensis israelensis) and VectoLex G (containing B. sphaericus) per liter could not induce symptoms of disease in I. basta (28). In addition, the Bacillus strain from the present study was readily cultured from both healthy and diseased I. basta in similar densities, suggesting that it is an unlikely primary pathogen.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The authors of that study speculate that bacterial pesticide pollution from agriculture may have introduced new bacteria that were pathogenic to sponges. Subsequent research with sponges and corals showed that addition of up to 5,000 g of the pesticides VectoBac G (containing B. thuringiensis israelensis) and VectoLex G (containing B. sphaericus) per liter could not induce symptoms of disease in I. basta (28). In addition, the Bacillus strain from the present study was readily cultured from both healthy and diseased I. basta in similar densities, suggesting that it is an unlikely primary pathogen.…”
Section: Discussionmentioning
confidence: 73%
“…All clone sequences from I. basta had low similarity to sequences in the NCBI database, indicating that I. basta hosts a novel microbial community. Similarly, Webster and coworkers (28) found that ca. 25% of the 16S rRNA-V6 tag sequences from I. basta were below the threshold for reliable assignment and may in fact represent previously unknown microbes.…”
Section: Discussionmentioning
confidence: 99%
“…The first used a commercial formulation of chlorpyrifos and reported coral mortality at 6 µg L -1 of the active ingredient (Te 1998). Negri et al (2009) found no effects of the biological insecticide Bacillus thuringiensis on adult and larval corals and sponges at 5000 µg L -1 . A recent study from Wecker and colleagues (2018) reported that the organochlorine insecticide chlordecone caused PeerJ reviewing PDF | (2020:05:48551:2:0:NEW 1 Jul 2020)…”
Section: Effects Of Pesticides On Coralsmentioning
confidence: 84%
“…In contrast, another study on adult colonies of P. damicornis demonstrated 50% mortality (LC50) to occur after 96-h exposure to 6 µg/L chlorpyrifos [92]. While most insecticides tested appear to negatively affect corals or their larvae, a recent study indicates that the "eco-friendly" larvicidal agent, Bacillus thuringiensis ssp israelensis (Bti), used extensively to control mosquitoes in the tropics, is harmless to coral larvae [93].…”
Section: Impactmentioning
confidence: 99%